Что есть «жизнь» и что из представлений о ней может следовать - Кордюм, В.А. (Проблемы управления и информатики, 2012)
Розвиток науки вийшов на рівень неформального взаємопроникнення її різних галузей і напрямів. У цьому зв’язку проведено аналіз можливої інтерпретації інтегральних рішень біології та рівня їх загальної універсальності. Основним положенням такої інтерпретації є формулювання уявлення про те, що всі події відбуваються в режимі програмно-причинно-наслідкового зв’язку. Це дозволяє принципово інакше, ніж сьогодні прийнято, підійти до розуміння й оцінки і нас самих, і оточуючого нас світу. The development of science has reached the level of informal interpenetration of its different fields and directions. In this connection, the analysis of possible interpretation of the integral solutions in biology and the level of their common universality was carried out. The main statement of such interpretation is the formulation of the view on the fact that all events are realized in the programmed-causal relationship. It gives the possibility to come to the understanding and evaluation of ourselves and the world around us in a completely different way comparing with the ways accepted today.